The Role and Contribution of Education Department of Dayah in Enhancing the Quality of Dayahs in East Aceh - Basri, Basri; Zainuddin, Zainuddin; Mudawali, Mudawali (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2023)
Dayah is a religious educational institution that has been a hallmark of the Aceh government since the sultanate. Throughout its existence, Dayah's presence in Aceh faded due to changes in the national education system which was general and conventional. Historically, the revitalization of Dayah emerged after the establishment of the Dayah Institute at the Aceh Province level which houses the Dayah Education Department at the regency and administrative city levels. The Dayah Education Department in Aceh emerged as a result of Aceh's special autonomy rights after obtaining a peace agreement with the Government of the Republic of Indonesia. The Dayah Education Department is a unique legal entity because it is not owned by other provinces in Indonesia. This article is included in field research that uses a qualitative approach. The method used is a phenomenological study of the existence of the Dayah Education Department, especially in East Aceh. Data was obtained through interviews, documentation, and direct observation. The research results show that the Dayah Education Department in East Aceh has an important role in improving the quality of Dayah in East Aceh, such as improving facilities and infrastructure; life skills training for students, as well as improving the quality of teachers and educational staff.